Pendampingan Pengolahan Mandaka Fermentasi melalui Variasi Waktu Fermentasi untuk Meningkatkan Kualitas Produk di Kecamatan Jekan Raya Kota Palangka Raya - Noor Hujjatusnaini; Mila Mila; Rafiq Ibnu Widyadana; Rafif Ibnu Widyadana (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
Jekan Raya Subdistrict, Palangka Raya City, has significant potential for the development of local fermented foods, particularly the traditional product mandai made from cempedak fruit peel. However, the seasonal availability of raw materials necessitates innovation using alternative ingredients with similar characteristics. This community service activity aimed to enhance community knowledge and skills in processing fermented mandaka using jackfruit peel as an alternative raw material, as well as to identify the effect of fermentation time variation on the organoleptic quality of the product. The implementation methods included counseling, demonstration, hands-on practice, and evaluation through pretest-posttest, organoleptic testing, and participant satisfaction and interest questionnaires. The results showed a 60% increase in participants’ knowledge, with the highest improvement observed in fermentation time and processing techniques. Organoleptic testing indicated that fermentation for 1×24 hours produced the best quality in terms of texture, color, aroma, and taste. Participant satisfaction was high (69–85%), and most participants (93%) expressed interest in developing the product as a business opportunity. This activity contributed to improving community capacity and opened opportunities for local economic development through innovation in fermented local food products.